2018
DOI: 10.1556/018.69.2018.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of capsaicin on the oxidative stress and dopamine content in the transgenic Drosophila model of Parkinson’s disease

Abstract: In the present study the effect of capsaicin was studied on PD model flies expressing human alpha synuclein. First the potential of scavenging superoxide anion and free radicals by capsaicin at doses of 20, 40, 80 and 100 μM was estimated. The PD flies were allowed to feed separately on the diet containg 20, 40, 80 and 100 μM of capsaicin, respectively, for 24 days. After 24 days of exposure, fly head homogenate was prepared from each group and was used to estimate glutathione (GSH), protein carbonyl (PC), dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…These PD flies displayed a progressive form of neurodegeneration characterized by loss of dopamine function, oxidative stress and impaired performance in the climbing assay. Reversal of the pathological changes occurred in a dose-dependent manner which confirmed the therapeutic potential of capsaicin through TRPV1 activation for PD treatment (Siddique et al, 2012(Siddique et al, , 2018.…”
Section: Trpv1supporting
confidence: 59%
“…These PD flies displayed a progressive form of neurodegeneration characterized by loss of dopamine function, oxidative stress and impaired performance in the climbing assay. Reversal of the pathological changes occurred in a dose-dependent manner which confirmed the therapeutic potential of capsaicin through TRPV1 activation for PD treatment (Siddique et al, 2012(Siddique et al, , 2018.…”
Section: Trpv1supporting
confidence: 59%
“…In our study the PD flies showed the loss of memory as measured by performing aversive phototaxis assay. The natural plant products have been shown to improve the memory functions in various experimental models 48 50 . Based on the results obtained in our present study the possible mode of protection by kaempferol has been depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Lemons can protect from Alzheihmer's disease by decreasing the MAO activity (Oyeleye et al, 2021). Capsaicin can also reduce the MAO activity in the Parkinson's model of D. melanogaster (Siddique et al, 2018). MAO can be quantified following Mcewen (McEwen, 1965).…”
Section: Biochemical Assaysmentioning
confidence: 99%